Assessing the long-term fragmentation of information systems research with a longitudinal multi-network analysis. Issue 4 (4th July 2019) - Khan, Gohar Feroz; Trier, Matthias
ABSTRACT: Over the decades, the evolving information systems (IS) research community and its academic output has greatly expanded. This paper offers an integrated analysis of multiple dimensions of network interconnectedness of the growing IS discipline. In line with the social and intellectual dimensions of the underlying theory of science, we synthesise multiple network views on authors, institutions, journal outlets, citations, and themes into a multi-dimensional knowledge network infrastructure analysis of collaborative networks of IS researchers and their academic output. We further introduce two fragmentation types to better address the dynamics of the IS discourse discussed in previous research. Based on a corpus of all 3587 AIS basket of 8 journal articles over 20 years, we use the analytical framework to study whether the fast growth of the IS discipline resulted in a reduced coherence of the overall academic collaboration and the research themes. The analysis reveals that the sampled IS researcher community developed a large core component with influential bridging people who mitigate fragmentation and centralisation. This IS community structure constitutes a valuable asset to cope with fragmentation tendencies in the intellectual dimension (research topics) resulting from many short-term topic bursts and from centralisation of conceptual terms.